TEACHING AND LEARNING WITH TECHNOLOGY: A THEORETICAL MODEL FOR GOOD EDUCATIONAL PRACTICES WITH ICT - Jesús Valverde Berrocoso; María del Carmen Garrido Arroyo; Rosa Fernández Sánchez (Ediciones Universidad de Salamanca, 2010)
<!-- @page { margin: 0.79in } P { margin-bottom: 0.08in } --> This article aims to define a theoretical explanatory framework for the integration of information technologies and communication technologies (ICT) in education from the perspective of teacher education. The initial and continuing training of teachers is characterized by a tendency towards "essentialisation" of technology and generation of users who do not usually think about educational uses of technology in their own contexts. Our research on the integration of ICT in the classroom has allowed us to observe the lack of connection between the personal and professional use of teachers of these technological tools, as well as the need for training is geared towards developing skills and knowledge to examine, in a critical manner, the educational implications of these new teaching aids. This article is based on the proposed Koehler & Mishra (2005, 2006, 2007 and 2008) called TPCK (Technological Pedagogical Content Knowledge) which is based on the construct of PCK Shulman (1987) to which is added the concept of "Technology" (T) to those of "Pedagogy" (P) and "Curriculum Content" (C). Connections and dynamic interactions between these three key components leading to different components to be considered in understanding the processes of integration of ICT in schools. Good educational practices with ICT are multidimensional and complex actions that require (1) understand the representation and formulation of concepts and procedures for their understanding through ICT, (2) develop constructivist teaching strategies that use ICT for teaching content curriculum, (3) know the difficulties in learning concepts and how ICT can help overcome them, and (4) knowing the students' prior knowledge and the epistemology of the curriculum to understand how ICT can be used to build on pre-existing knowledge and develop new epistemologies. These skills clearly go beyond the isolation that has an expert in a curriculum (teacher of a discipline), an expert in IT (engineer), or an expert teacher (educational technologist), so the teacher education requires a rethinking approaches and current practices